Rapid SDHB-variant gastric GIST progression with thoracic extension and multiple pulmonary metastases - Shiro Matsumoto; Hironori Yamaguchi; Takehiro Kagaya; Ayumi Matsumoto; Noriyoshi Fukushima; Yoshinori Hosoya (Current Problems in Cancer: Case Reports)
We describe a rare case of SDHB-variant gastric gastrointestinal stromal tumor (GIST) in a 37-year-old woman. The tumor exhibited an unusually aggressive clinical course originating from the lesser curvature of the stomach and extending through the esophageal hiatus into the thoracic cavity. Imaging revealed multiple pulmonary nodules without hepatic or lymph nodal metastases. Immunohistochemical analysis showed positivity for KIT and DOG1, and targeted sequencing identified a pathogenic SDHB R46Q variant. Surgical resection was deemed infeasible due to tumor size and location, and the patient received sequential systemic therapies including imatinib, sunitinib, regorafenib, and pimitespib. However, both primary lesion and pulmonary metastases demonstrated rapid progression, and the patient died within six months of treatment initiation. Succinate dehydrogenase (SDH)-deficient GISTs often involve hepatic and lymph node metastases but generally follow an indolent clinical course. However, this case demonstrated exclusive pulmonary metastases and rapid progression. The atypical metastatic pattern and aggressive course suggest biological heterogeneity within SDH-deficient GISTs and underscore importance of early molecular profiling and close clinical monitoring.